Mechanism and therapeutic potential of traditional Chinese medicine extracts in sepsis - Fu, Chen-Fei; Li, Jian-Long; Chen, Jia-Wei; Liang, Hao; Zhao, Wen-Rui; He, Shi-Yu; Ma, Xiao-Wei; Yang, Xiao-Fan; Wang, He-Lin (Frontiers in Pharmacology, 2024)
Sepsis is a complex syndrome characterized by multi-organ dysfunction, due to the presence of harmful microorganisms in blood which could cause mortality. Complications associated with sepsis involve multiple organ dysfunction. The pathogenesis of sepsis remains intricate, with limited treatment options and high mortality rates. Traditional Chinese medicine (TCM) has consistently demonstrated to have a potential on various disease management. Its complements include reduction of oxidative stress, inhibiting inflammatory pathways, regulating immune responses, and improving microcirculation. Traditional Chinese medicine can mitigate or even treat sepsis in a human system. This review examines progress on the use of TCM extracts for treating sepsis through different pharmacological action and its mechanisms. The potential targets of TCM extracts and active ingredients for the treatment of sepsis and its complications have been elucidated through molecular biology research, network pharmacology prediction, molecular docking analysis, and visualization analysis. Our aim is to provide a theoretical basis and empirical support for utilizing TCM in the treatment of sepsis and its complications while also serving as a reference for future research and development of sepsis drugs.